Alternate non-stop migration strategies of pied flycatchers to cross the Sahara desert - Ouwehand, Janne (Biol Lett, 2016)
Each year more than two billion songbirds cross the Sahara, but how they perform this formidable task is largely unknown. Using geolocation tracks from 27 pied flycatchers, a nocturnally migrating passerine, we show that most birds made diurnal flights in both autumn and spring. These diurnal flights were estimated to be part of non-stop flights of mostly 40–60 h. In spring, birds flew across the Sahara, while autumn migration probably circumpassed part of the desert, through a long oversea flight. Our data contradict claims that passerines cross the Sahara by intermittent flight and daytime resting. The frequent occurrence of long non-stop flights to cross the desert shows migrants' physiological abilities and poses the question why this would not be the general migration strategy to cross the Sahara.